Relationship between Duration of Use of 3 Months of Injectable Contraceptives and Weight Gain in KB Acceptors at the Independent Practice of Midwife C. Yuni Anggarini - Putu Dewi Rahayu Ningsih; Chentia Misse; Zesika Intan (Lembaga Pengembangan Kinerja Dosen, 2025)
43.8% of contraception acceptors in Lampung Province in 2022 used injective contraception. 69.2% of them experienced a 5 kg body weight increase side effect. This may lead to obesity. This research aimed to determine the correlation between the duration of accepting a contraceptive injection every 3 months and contraception acceptors' body weight increase in C. Yuni Anggraini Private Midwives Clinic. This quantitative research used a cross-sectional design. The population was 108 respondents. 58 respondent samples were taken using consecutive sampling. The data were analyzed using univariate analysis with a frequency distribution table and bivariate analysis with a chi-squared test. 22 respondents (37.9%) accepted a contraceptive injection every 3 months for 1-2 years and 22 (37.9%) accepted a contraceptive injection every 3 months for more than 2 years. 42 respondents (72.4%) experienced body weight increases. The bivariate analysis result derived a p-value of 0.024. This indicated a correlation between the duration of a contraceptive injection every 3 months and contraception acceptors' body weight increase in C. Yuni Anggraini Private Midwives Clinic. A contraceptive injection every 3 months for a long time can increase contraceptive acceptors' body weight increase.